Influences of power on suppliers' adaptation for sustainability - a dyadic perspective - Roman Buck (2014)
In this study, the adaptive behaviour towards sustainability initiatives is investigated in interorganizational exchange relations. To do so, Small and Medium-sized Enterprises (SMEs) in a supplier role that experienced a situation where a buyer asked them to adapt to a certain sustainability initiative are asked about their power relation with their buyer. During this process, suppliers perceived dependence and buyers perceived power are compared, and the outcome of these measures on the adaptive behaviour towards sustainability is modelled. In order to explain the power relation in the dyad in more detail, the framework of the bases of power as initially introduced by French Jr. and Raven (1959) is integrated in the analysis. Sustainability in the current globalised business environment needs to be tackled on a systems level rather than by focusing on a site. The purpose of this research is to shed some light on the permeation of sustainability initiatives through the upward supply chain. The current academic literature about the drivers of Sustainable Supply Chain Management (SSCM) point towards the buyers as a powerful driver. Therefore, this driver is scrutinized in detail with the aims to: a) deliver practical advice on how to improve sustainability permeation from a buyer s perspective; and b) contribute to academic knowledge by dismantling and analysing the mechanism behind buyer power driven sustainability permeation. An online questionnaire was deployed to collect data from SMEs in a supplier role. The participants were contacted and reminded via email. The questionnaire is based on established instruments to measure suppliers dependence (Bode et al., 2011) and the bases of power (Raven et al., 1998). The quantitative analysis of the responses to the questionnaires is built around a mediation model with suppliers dependence as Independent Variable (IV), the binary outcome of sustainability adaptation as Dependent Variable (DV) and two mediators representing the magnitude of hard and soft power bases in the dyadic exchange relation. The established framework of the bases of power is a suitable instrument to explain the relationship between a supplier s adaptive behaviour towards sustainability and its dependence on its buyer. Measurements solely of how a supplier perceives its dependence on the buyer do not explain the adaptive behaviour of a supplier towards a buyer-requested sustainability initiative. Introducing the bases of power framework and distinguishing between soft and hard bases of power explains why suppliers experiencing hard power bases are more likely to reject a buyer-requested sustainability initiative, whereas suppliers experiencing soft power bases show a significantly higher acceptance of buyer-requested sustainability initiatives. Without dismantling the black box power, the observation that the two effects neutralize each other if not distinguished cannot be made. The original contribution to knowledge is the mechanism behind power in dyadic exchange relations and how this mechanism conduces to the permeation of sustainability through the supply chain. Knowing about the different pathways hard and soft, and their opposite effect on sustainability adaptation, advances knowledge in the SSCM literature and provides guidance for practitioners.